2022
DOI: 10.1007/978-3-030-94285-4_3
|View full text |Cite
|
Sign up to set email alerts
|

A Cybersecurity Guide for Using Fitness Devices

Abstract: The popularity of wearable devices is growing exponentially, with consumers using these for a variety of services. Fitness devices are currently offering new services such as shopping or buying train tickets using contactless payment. In addition, fitness devices are collecting a number of personal information such as body temperature, pulse rate, food habits and body weight, steps-distance travelled, calories burned and sleep stage. Although these devices can offer convenience to consumers, more and more repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…How might the privacy of a hug-from-a-distance system be threatened? By leakage of the personal data from the device or from an app; by an attacker sending hugs as a manin-the-middle to the unsuspecting partner; by the hug system's presence or usage being exposed to bystanders, either through network activity (most wearable devices use Bluetooth, which is not very secure) [10] or by attention's being drawn to its physical presence. The author of the design fiction that inspired the Gallery Necklace was the only male in the group; we gave his necklace a minimalist style in keeping with the style of his paper prototypes, but also to avert the risk of hostile reactions from other men.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…How might the privacy of a hug-from-a-distance system be threatened? By leakage of the personal data from the device or from an app; by an attacker sending hugs as a manin-the-middle to the unsuspecting partner; by the hug system's presence or usage being exposed to bystanders, either through network activity (most wearable devices use Bluetooth, which is not very secure) [10] or by attention's being drawn to its physical presence. The author of the design fiction that inspired the Gallery Necklace was the only male in the group; we gave his necklace a minimalist style in keeping with the style of his paper prototypes, but also to avert the risk of hostile reactions from other men.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…More studies have concluded that it is important to teach users about the correct use of this technology because most of the recommendations always go to the manufacturers. They propose some guidelines to instruct about wearable devices [ 38 ] and state the need for standards in the wearable industry [ 36 ].…”
Section: Iot Vulnerabilities and Challengesmentioning
confidence: 99%